Effect of anode and cathode flow field geometry on passive direct methanol fuel cell performance. (10th March 2015) - Gholami, Omid; Imen, S.Javad; Shakeri, Mohsen
Abstract: In this paper, the effect of cathode flow field geometry on a passive direct methanol fuel cell (DMFC) performance at various concentrations of methanol is studied. Three cells with perforated current collector, parallel channels and trapezoidal channels with opening to downward current collector at the cathode side are tested at 2 to 5 molar concentrations of methanol. In order to maintain equal conditions on the anode side, the trapezoidal channels with opening to upward is used in all three cells. By placing the cathode flow field pattern on the anode flow field pattern, four zones are defined and the role of these areas on the performance of each cell at concentrations of 2 to 5 molar are investigated. It is found that the zones where the anode's open area placed directly in front of the cathode's open area has a considerable effect on the methanol cross over, and also the zones which anode and cathode current collector's walls placed on each other has more effect on the amount of surface contact.